A comparative study of learning outcomes for hearing-impaired foundation phase learners - Aisha Casoojee; Katijah Khoza-Shangase; Amisha Kanji (South African Journal of Childhood Education, 2024)
Background: Two intervention approaches are implemented in South Africa to alleviate the deleterious consequences of congenital or early onset hearing impairment on language acquisition and subsequent poor learning outcomes.